1996
DOI: 10.1128/jvi.70.9.5902-5908.1996
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for kissing-loop-mediated dimerization of human immunodeficiency virus RNA

Abstract: Sequences from the 5 end of type 1 human immunodeficiency virus RNA dimerize spontaneously in vitro in a reaction thought to mimic the initial step of genomic dimerization in vivo. Dimer initiation has been proposed to occur through a "kissing-loop" interaction involving a specific RNA stem-loop element designated SL1: the RNA strands first interact by base pairing through a six-base GC-rich palindrome in the loop of SL1, whose stems then isomerize to form a longer interstrand duplex. We now report a mutationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
90
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(105 citation statements)
references
References 23 publications
8
90
0
Order By: Relevance
“…The 9–nucleotide loop contains a self‐complementary hexameric sequence GCGCGC (Lai isolate) or GUGCAC (Mal isolate) flanked by two adenines (Lai) or by an adenine and a guanine (Mal) on its 5′side and one adenine on its 3′ side. The dimeric structure seems to be essential for infectivity,1 and the role of the self‐complementary hexameric sequence and of the three flanking purines is crucial 2. It has been shown that the dimerization process is involved at different steps of the replication cycle of the virus such as recombination during reverse transcription,3–6 gag gene translation,7–9 and selective encapsidation of the genome in the viral particles 10.…”
Section: Introductionmentioning
confidence: 99%
“…The 9–nucleotide loop contains a self‐complementary hexameric sequence GCGCGC (Lai isolate) or GUGCAC (Mal isolate) flanked by two adenines (Lai) or by an adenine and a guanine (Mal) on its 5′side and one adenine on its 3′ side. The dimeric structure seems to be essential for infectivity,1 and the role of the self‐complementary hexameric sequence and of the three flanking purines is crucial 2. It has been shown that the dimerization process is involved at different steps of the replication cycle of the virus such as recombination during reverse transcription,3–6 gag gene translation,7–9 and selective encapsidation of the genome in the viral particles 10.…”
Section: Introductionmentioning
confidence: 99%
“…Ostensibly, dimer formation would occur through a kissing hairpin mechanism by which the two RNAs would form an initial loop-loop contact based on complementary antiparallel base pairing followed by the generation of a stable intermolecular structure composed of hydrogen-bonded nucleotides in the stem regions of the hairpin (29,38,41,44). In support of this model, disruption of the palindromic sequence in the hairpin abrogates in vitro dimerization (12,20,29,38,41,44).…”
mentioning
confidence: 95%
“…Short synthetic retroviral RNAs can spontaneously dimerize in vitro under certain conditions (4,6,8,11,12,14,15,20,27,29,34,41,(43)(44)(45), and the efficiency of dimerization can be enhanced by the viral nucleocapsid (NC) protein (14)(15)(16). Based on studies of in vitro dimer formation with deletion and substitution mutations, the presumptive primary DLS of human immunodeficiency virus type 1 (HIV-1) has been mapped to a region near the major splice donor, which is located just proximal to the beginning of the gag gene (4,34,45).…”
mentioning
confidence: 99%
“…The dimer linkage site is located near the 5′‐terminus sequence in the main packaging domain, which has been predicted to contain four stem‐loops SL1, SL2, SL3, and SL4 involved in packaging of the unspliced transcript viral RNA 10–16. SL1 is the largest one (35 nt) and is thought to contain the dimer initiation site (DIS), which corresponds to a 6 nucleotide (nt) palindrome sequence located in a 9 nt apical loop 17–19. This loop is complemented with two and one purine on the 5′ and 3′ sides of DIS, respectively, flanking the palindrome (Figure 1).…”
Section: Introductionmentioning
confidence: 99%